Implementation of Prophetic Education in Developing Students' Spiritual Intelligence in Islamic Religious Education Subjects at SMAN 1 Cangkringan Sleman Yogyakarta - Arifqi Faturrahman; M. Hajar Dewantoro (Didaktika: Jurnal Kependidikan, 2024)
Students' divine intelligence is something that is important to develop optimally so that students have good morals in the environment where they live. One of the things that influences students' divine intelligence is the school environment. Schools must make optimal efforts to increase the divine intelligence of their students, one of which is by implementing prophetic education in the school. In implementing prophetic education, those who play a role are the school principal, teachers and students themselves. In this research, researchers used a qualitative approach. Data collection in this research used two methods, namely interviews and documentation carried out at SMA N 1 Cangkringan. Data analysis in this research uses data collection, data reduction, data presentation, and drawing conclusions. The results of the research are that the principal at SMAN 1 Cangkringan has implemented his role well, starting from educating students problems related to the development of students' spiritual intelligence in various meeting forums. Religious teachers also take part in implementing spiritual activities in the school environment. Apart from that, religious teachers motivate students regarding the importance of social development integrated with religious understanding, such as the importance of friendship, helping each other in religion, doing good to each other and so on. Students at SMAN 1 Cangkringan, apart from studying, also really apply the attitude of respect taught by the school environment. Students obey school regulations as a sense of responsibility and habituation of good attitudes.